The soft skills capability among office management students at UiTM Pahang, Jengka Campus / Fatimah Mohamed Razali, Rosni Kuna and Suhana Mat Samberi - Mohamed Razali, Fatimah; Kuna, Rosni; Mat Samberi, Suhana (2009)
Soft skill can be defined as an intra-personal and interpersonal skills and traits that are required to thrive in the workplace. Soft skills are personal attributes which enhance an individual's interactions, job performance and career prospects. There are many dimensions included in soft skills. But, this study focuses on the soft skills capability among Office Management (OM) students at UiTM Jengka, Pahang based on five dimensions of soft skills such as the communication skills, interpersonal skills, leadership skills, adaptability skills, and time management. The main aim of this study was to identify whether the student of Office Management of Faculty Office Management and Technology aware about those soft skill capability which are required by employers and to identify whether they posses those dimensions of soft skill. The result revealed that most of the students were aware on these issues. Finally, recommendations were also included at the end of this report.